Offer of biosimilar drugs to the caja costarricense de seguro social: possible economic impact for social security - Castro Cambronero, Ariel (2017)
Aim: As of 2006, the market for biosimilars has grown globally. We sought to determine the feasibility of offering biosimilar drugs to the Caja Costarricense de Seguro Social (CCSS, for its acronym in Spanish), assessing its possible economic impact. Methods: A review of the commercial basis of data of the CCSS was made to know about the purchase of biological products by this institution. A search was made for biosimilars registered in countries governed by regulatory authorities of high health surveillance. And a study of the purchase prices of biosimilar drugs by the CCSS was carried out.Results: The antineoplastic and immunomodulatory agents group was the largest budget investment by 2015, and trastuzumab 440 mg and rituximab 500 mg accounted for 58,64% of the money spent for the purchase of biological drugs. In addition, there are currently 10 active substances approved by the regulatory authorities of high health surveillance. Finally, for biosimilar products purchased by CCSS, their price has decreased over time (57% for epoetin α and 61% for filgrastim, compared to the historical purchase value). Conclusion: Offering biosimilar drugs to the CCSS may become more frequent in the short term, due to the economic savings resulting from their purchase.